Relocation intention to smart retirement village among elderly Malaysians - Sarwar, Abdullah Al-Mamun; Mhd Sharif, Suhaimi; Ahmad Hakim, Shabir; Khaled Altamimi, Yousef (Allied Business Academies, 2021)
The rapid growth of the ageing population has contributed to an increased attention towards the provision of smart retirement village (SRV). SRV is a new form of housing that is a trustworthy solution for the elderly’s retirement lifestyle. Many studies have conducted in the past to examine the factors that influence elderly intention to relocate to SRV, however, the findings often contradicted to each other. As such, research outcome cannot be generalized due to the complexity of consumers in different cultural, time and geographical context. Therefore, this study focuses on finding of factors that influence the relocate intention of elderly in Malaysian SRV. This study extends from the theory of planned behaviour (TPB) by adding two variables (i.e. environmental concern and rewards) to measure the elderly relocation intention. In this study, a convenience sampling strategy is used to gather data. The 259 usable data collected from the survey were analysed using multiple regressions. The findings show that intention to relocate to SRV depends on attitude, social norm and rewards. The other two variables; perceived behavioural control and environmental concern were found to have no significant impact on the relocate intention of SRV. SRV service providers may use the results and customize marketing materials for their individual services.